PID Comes Full Circle: Applications of V(D)J Recombination Excision Circles in Research, Diagnostics and Newborn Screening of Primary Immunodeficiency Disorders - Van Zelm, Menno C.; Van Der Burg, Mirjam; Langerak, Anton W.; Van Dongen, Jacques J. (Frontiers in Immunology, 2011)
The vast majority of patients suffering from a primary immunodeficiency (PID) have defects in their T- and/or B-cell compartments. Despite advances in molecular diagnostics, in many patients no underlying genetic defect has been identified. B- and T-lymphocytes are unique in their ability to create a receptor by genomic rearrangement of their antigen receptor genes via V(D)J recombination. During this process, stable circular excision products are formed that do not replicate when the cell proliferates. Excision circles can be reliably quantified using real-time quantitative (RQ-)PCR techniques. Frequently occurring δREC–ψJα T-cell receptor excision circles (TRECs) have been used to assess thymic output and intronRSS–Kde recombination excision circles (KREC) to quantify B-cell replication history. In this perspective, we describe how TRECs and KRECs are formed during precursor- T and B cell differentiation, respectively. Furthermore, we discuss new insights obtained with TRECs and KRECs and specifically how these excision circles can be applied to support therapy monitoring, patient classification and newborn screening of PID.